Carboplatin hypersensitivity: evaluation and successful desensitization protocol. (August 2014) - Bruchim, Ilan; Goldberg, Arnon; Fishman, Ami; Confino-Cohen, Ronit
Aim: Carboplatin-induced immediate hypersensitivity reactions are relatively common among patients with gynecological malignancies. Once this occurs, the patient might be at risk for future carboplatin-induced reactions. This study evaluated the efficacy of allergic consultation, carboplatin skin testing and desensitization as a single intervention strategy in this population.Methods: Patients with a well-documented immediate reaction to carboplatin were offered allergy consultation, carboplatin skin testing and a desensitization plan in a single visit between scheduled chemotherapy sessions.Results: Fifty-five patients with an immediate reaction were evaluated. After allergist assessment, 44 (89%) of 49 patients skin tested had a positive result. A total of 207 carboplatin desensitization cycles were administered to 49 women. Among them, 10 patients had a mild immediate hypersensitivity reaction during desensitization. Five patients subsequently tolerated carboplatin administered in the prolonged desensitization protocol.Conclusions: In the data presented, we propose a strategy that is both cost effective and very convenient for the patient. The diagnostic procedure, including allergist consultation and skin test, can be completed in less than 2 h. In most cases where carboplatin is indispensable, desensitization can be administered without overnight hospitalization.